2013
DOI: 10.1097/iae.0b013e31829234e6
|View full text |Cite
|
Sign up to set email alerts
|

Outer Retina Analysis by Optical Coherence Tomography in Cone-Rod Dystrophy Patients

Abstract: SD-OCT scans demonstrated complete absence of the interdigitation zone in patients with cone-rod dystrophy. Consistent with the known histology of animal models of cone dystrophy, this finding may represent abnormal outer retinal morphology, including an absence of the outer segments themselves or a defective or absent interdigitation between the apical processes of the retinal pigment epithelium with the cone outer segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 15 publications
3
21
1
Order By: Relevance
“…ERG is a more sensitive technique and can be used to diagnose CD earlier than is possible using current diag nostic techniques (1) . A variety of mechanisms, such as defective outer segment morphogenesis, protein transport along the cilium, phototransduction, or cellular interaction, have been suggested as being responsible for cone dysfunction (2) . The retinal pathology of CD occurs mainly between the photoreceptor outer segment and retinal pigment epithelium (RPE) layer (1) .…”
Section: Introductionmentioning
confidence: 99%
“…ERG is a more sensitive technique and can be used to diagnose CD earlier than is possible using current diag nostic techniques (1) . A variety of mechanisms, such as defective outer segment morphogenesis, protein transport along the cilium, phototransduction, or cellular interaction, have been suggested as being responsible for cone dysfunction (2) . The retinal pathology of CD occurs mainly between the photoreceptor outer segment and retinal pigment epithelium (RPE) layer (1) .…”
Section: Introductionmentioning
confidence: 99%
“…The IZ line is vulnerable to damage and is disrupted in virtually every kind of macular diseases [5] [20]. Disruption of the IZ line has been reported both in RP [12] and in CRD [19], but the difference between these retinal dystrophies is not known. The results of the current study showed that the IZ line is visible in some patients with RP, but not in any patients with CRD, even though patients had similar visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…in RP [9][10][11][12], cone dystrophy [13][14][15][16][17], and CRD [18]. In addition, a recent study suggested that the IZ line is useful in differentiating between different types of photoreceptor degenerations because cone photoreceptors are primarily impaired in CRD [19]. However, it is not known if changes of IZ line is specific to CRD because IZ appearance on OCT is sensitive to any kind of photoreceptor damage [20].…”
Section: Introductionmentioning
confidence: 99%
“…A disruption or loss of the macular inner/outer segments junction of the photoreceptors was shown in achromatopsia [3,11,12]. Absence of an interdigitation zone was found in cone-rod dystrophy [13].…”
mentioning
confidence: 99%
“…Optical coherence tomography and FAF imaging in children with nystagmus is challenging due to unpredictable co-operation and unstable fixation in nystagmus [6,20,21]. The groups studied so far have usually been small and mostly included older children and adults using various OCT machines [9][10][11][12][13][22][23][24]. Similarly, the retinal thickness val-ues of healthy children in the literature applied only to a group of children studied, while generally accepted normative values for the paediatric population are not yet available [25][26][27][28][29].…”
mentioning
confidence: 99%